Studies On A Trypsin Inhibitor From The Seeds Of Murraya Koenigii - TEJAS S.KULKARNI,; SUSHMA G. SABHARWAL, (International Journal of Pharma and Bio Sciences, 2012)
A novel proteinaceoustrypsin inhibitor from the seeds of Murrayakoenigii (Indian curry leaf tree) (MKTI)was isolated and purified to homogeneity by ion exchange chromatography followed by gel filtration chromatography on Sephadex G-75. The specific inhibition of the trypsin amongst the other serine proteases suggests that Murrayakoenigiitrypsin inhibitor(MKTI) may belong to the Kunitz-type protease inhibitor family. The molecular mass of the novel cysteineless inhibitor was determined to be 21601.44 Daltons by MALDI-TOF. Kinetic studies revealed that Murrayakoenigiitrypsin inhibitor is a competitive inhibitor having 1:1 stoichiometry of binding with trypsin. The trypsin inhibitor of the seeds of Murrayakoenigii, a non-glycoprotein, exists as a monomer under physiological conditions with 4.44% α helical content, 44.17% β sheet and 51.42% random coil structure as determined by circular dichroism studies.